2010
DOI: 10.1038/cddis.2010.7
|View full text |Cite
|
Sign up to set email alerts
|

JNK phosphorylates Yes-associated protein (YAP) to regulate apoptosis

Abstract: Yes-associated protein (YAP) regulates DNA damage and chemosensitivity, as well as functioning as a pro-growth, cell size regulator. For both of its roles, regulation by phosphorylation is crucial. We undertook an in vitro screen to identify novel YAP kinases to discover new signaling pathways to better understand YAP's function. We identified JNK1 and JNK2 as robust YAP kinases, as well as mapped multiple sites of phosphorylation. Using inhibitors and siRNA, we showed that JNK specifically phosphorylates endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
114
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(120 citation statements)
references
References 43 publications
2
114
0
2
Order By: Relevance
“…As shown in Figure 1, we confirmed 4 potential serine phosphorylation sites in YAP1 by Lats1/2 at 61, 109, 127 and 164; 25,26 4 potential phosphorylation sites by JNKs at T119, S138, T154 and S317; 27 and 5 potential phosphorylation sites at T119, S128, S138, S289 and S367 by CDK1. 28,29 More importantly, we identified several additional serine/threonine phosphorylation sites (Fig.…”
Section: Ip-mass Spectrometry Analysis Of Yap1 Post-translational Modsupporting
confidence: 63%
See 1 more Smart Citation
“…As shown in Figure 1, we confirmed 4 potential serine phosphorylation sites in YAP1 by Lats1/2 at 61, 109, 127 and 164; 25,26 4 potential phosphorylation sites by JNKs at T119, S138, T154 and S317; 27 and 5 potential phosphorylation sites at T119, S128, S138, S289 and S367 by CDK1. 28,29 More importantly, we identified several additional serine/threonine phosphorylation sites (Fig.…”
Section: Ip-mass Spectrometry Analysis Of Yap1 Post-translational Modsupporting
confidence: 63%
“…14 Also, c-Jun N-terminal kinases (JNKs) phosphorylates YAP at T119, S138, T154, S317 and T362 and enhances its stabilization of DNp63. 27 Last, the CDK1 phosphorylates YAP at T119, S128, S138, S289 and S367, which promotes mitotic defects and decreases YAP mediated anti-apoptosis potential induced by the anti-tubulin drugs. 28,29 In the present study, we confirmed most of these post-translational modifications in YAP (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…During the Our findings indicate that dysregulation of DNp63 triggered by YAP inactivation is functionally related to lung cancer transdifferentiation in the context of LKB1 mutant ADC and Ad-SCC with mixed pathologies. Previous study has shown that YAP can bind to and stabilize p63 in keratinocytes to protect damage from ultraviolet irradiation 42 . Interestingly, we find that YAP and DNp63 show a reverse correlation in lung ADC and SCC, which might be resulted from the default transcriptional repression of DNp63 by YAP.…”
Section: Discussionmentioning
confidence: 99%
“…42 This suggests that the contextdependent role of YAP in preventing or promoting stressinduced apoptosis is conserved in Drosophila Yki. The exact molecular nature of the context-dependent cue(s) that determine this 'apoptotic switch' 57 remain to be established, but are likely to involve posttranslational modification of Yki and/or p53, as well as the activation status of other signaling cascades, such as the JNK pathway 64 or c-Abl, 65 both of which have been shown to drive YAP-dependent apoptosis. The conserved nature of this dual behavior of Yki in damage response may reflect its proposed ancient function as a mediator of tissue damage repair.…”
Section: Discussionmentioning
confidence: 99%